A Novel Digital Certificate Based Remote Data Access Control Scheme in WSN. (2nd August 2015) - Liang, Wei; Ruan, Zhiqiang; Zhou, Hongbo; Xie, Yong
Abstract : A digital certificate based remote data access control scheme is proposed for safe authentication of accessor in wireless sensor network (WSN). The scheme is founded on the access control scheme on the basis of characteristic expression (named CEB scheme). Data is divided by characteristics and the key for encryption is related to characteristic expression. Only the key matching with characteristic expression can decrypt the data. Meanwhile, three distributed certificate detection methods are designed to prevent the certificate from being misappropriated by hostile anonymous users. When a user starts query, the key access control method can judge whether the query is valid. In this case, the scheme can achieve public certificate of users and effectively protect query privacy as well. The security analysis and experiments show that the proposed scheme is superior in communication overhead, storage overhead, and detection probability.